The Moderating Role of Auditor Experience in The Relationship Between Audit Pressure and Audit Quality - Tinyase, Kwaku Ohemeng; Ocansey, Evans Osborn Nene Daker; Asamoah, Felix Oppong (Archives of Business Research, 2025)
Audit-related corporate failures have raised concerns about the quality of audit practices. For several scholars, audit time pressure remains a primary determinant of audit quality, although there is debate regarding the critical role of auditors’ experience. While studies have aimed to understand this interplay, most research originates from high-income nations, which limits empirical evidence in resource-constrained contexts like Ghana. This study explores the moderating role of auditor experience in the relationship between audit time pressure and audit quality in Ghana, an emerging economy. A cross-sectional research design was employed, with data collected from a diverse sample of 350 audit practitioners in Accra, Ghana, using a self-administered online questionnaire. The measurement model was validated using confirmatory factor analysis, and the hypothesised relationships were tested using linear regression and moderation analysis. The findings reveal that audit time pressure has a significant positive effect on audit quality when considered independently. However, when auditor experience is introduced, the effect of audit pressure becomes negative and statistically insignificant, while auditor experience shows a strong positive and significant relationship with audit quality. Furthermore, the interaction between audit pressure and auditor experience is positive and significant, indicating that auditor experience moderates the relationship between audit pressure and quality. Specifically, as auditor experience increases, the positive effect of audit pressure on audit quality increases. This study pioneers enquiries into the drivers of audit quality in sub Sahara Africa, particularly in the investigation of the role of auditor experience in addressing the effects of time pressure. These findings contribute to the understanding of how auditor attributes function as strategic resources under constrained conditions in emerging economies and provide insights for audit firms and regulators on the importance of investing in professional development to enhance auditor expertise.